Social and daily kolomyika: traditional understanding of social reality (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
This paper investigates the problem of traditional social reality, reflected in the genre of kolomyika. Folklore seems as a dynamic process that involves the transformation of traditional assessments of reality according to historical, political, social and psychological characteristics of epoch.
Keywords: social and daily folklore; kolomyika; tradition; transformation